Studi Optimalisasi Fasilitas Parkir Chandra Department Store Pusat, Bandar Lampung - Riska Adelia Riska Adelia; Muhammad Karami; Siti Anugrah Mulya Putri Ofrial (REKAYASA: Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2024)
Chandra Department Store Bandar Lampung is one of the areas where parking issues presented on by vehicles stationed on the side of the road have severely hampered the rate of vehicle traffic. This study aims to assess how Central Chandra Department Store’s parking performance. The method applied in this research is a descriptive analysis approach, which is then followed by qualitative approach. The research was performed on Sunday, October 01, 2023, from 08:00 AM to 10:00 PM WIB, for a total of 840 minutes, at the Chandra Department Store parking area. According to the research’s findings, the great majority of parked cars is 235, with a parking index of 49%, while the total number of parked motorcycles is 89, with a parking index of 22%. The number of cars in the parking area is 2249, with a PTO of 4,73 vehicles/day/space, while the number of motorcycles is 1045, with a PTO of 2,61 vehicles/day/space. The average amount of time for a parking car is 123 minutes, while for motorcycles is 87 minutes. The capacity of parking space available are 3234 for cars and 3862 for motorcycles. Using a comparison of the capacity number that is higher than the parking volume, it can be concluded that the Central Chandra Department Store parking area is still equipped to satisfy parking demands.